The relationship between attachment and depression among college students: the mediating role of perfectionism - Fang, Fang; Wang, Jingwen (Frontiers in Psychology, 2024)
Objectives Explore the relationship between adult attachment and depression among college students, and the mechanism of perfectionism. Study design Questionnaire survey. Methods A questionnaire survey was conducted nationwide, totally 313 valid questionnaires were received. The survey collected information such as adult attachment (Adult Attachment Scale, AAS), depression (The Center for Epidemiologic Studies Depression Scale, CESD), and perfectionism (The Frost Multidimensional Perfectionism Scale, FMPS). Then used SPSS26.0 to analyze the collected data. Results There were significant differences in perfectionism and depression between secure attachment and insecure attachment in college students. Perfectionism plays a partial mediating role in the relationship between the close-depend composite dimension, anxiety dimension of attachment and depression. Conclusion The closeness-dependence dimension of attachment significantly and negatively predicted perfectionism and depression; the anxiety dimension of attachment significantly and positively predicted perfectionism and depression; and perfectionism partially mediated the effect of both the closeness-dependence dimension of attachment on depression and the anxiety dimension of attachment on depression. Attachment can directly affect college students’ depression, but also indirectly through perfectionism.